The effects of antioxidants on various body systems and physical activity - a literature review on Astaxanthin - Kusak, Natalia; Rudziński, Gracjan; Pażyra, Aldona; Żak, Natalia; Jaworska, Barbara; Stanicki, Paweł (Quality in Sport, 2024)
Astaxanthin is an organic fat-soluble compound from the xanthophyll group derived mainly from marine organisms. It has greater antioxidant properties than vitamins e, c and beta-carotene. It may have potential applications in various areas of medicine and dietetics. The safe daily dose appears to be 6-8 mg per day. Its use may be beneficial in cardiology by lowering insulin resistance, improving lipid profile and reducing the extent of myocardial infarction. In addition, it improves cognitive function and has beneficial effects on skin properties such as texture and hydration. Its positive effects on visual acuity have also been proven. Its use can increase fat burning during aerobic exercise and increase physical performance during exercise. Considering the available research results, astaxanthin seems to be a promising supplement with strong antioxidant properties. Most of the studies, however, were conducted on animals and more human studies are needed. The purpose of this work is to summarize the available knowledge regarding this unique substance. The article reviews studies and scientific papers available in PubMed databases on Astaxanthin for the period 2010-2023.